The Canadian Optimal Therapy of COPD Trial: Design, Organization and Patient Recruitment - Shawn D Aaron; Katherine Vandemheen; Dean Fergusson; Mark FitzGerald; Francois Maltais; Jean Bourbeau; Roger Goldstein; Andrew McIvor; Meyer Balter; Denis O'Donnell (Canadian Respiratory Journal)
BACKGROUND: There are no published studies that have assessed whether adding long-acting beta 2-agonist bronchodilators and/or inhaled steroids to chronic therapy with tiotropium would provide additional clinical benefit to patients with moderate to severe chronic obstructive pulmonary disease (COPD).